"To leave or not to leave" is the crucial question of authority for housing adaptation in the Greater Jakarta Metropolitan Area. Issue 8 (17th November 2022) - Adianto, Joko; Gabe, Rossa Turpuk
ABSTRACT: This study aims to identify the prominent factors of housing preferences, satisfaction and adjustment (mobility and adaptation) of residents of the Greater Jakarta Metropolitan Area (GJMA), and investigate their interrelationship as an integrated interaction of residents with housing conditions. This quantitative study in the GJMA identifies housing affordability as the most important housing preference for the residents, followed by neighborhood, space and location norms. The study has found that housing adaptations are effectively delivered to cope with the housing deficit experienced due to the ever-changing life cycle to postpone the need to move house, which requires the implicit authority from the homeownership or family ties. However, in the unaffordable housing market with homeownership, this study suggests a massive quantity of affordable rental housing provision across the city is required to deal with the housing mobility issue to cope with the perpetual housing deficit of the residents through their dynamic life cycle.